1992
DOI: 10.1002/cne.903220306
|View full text |Cite
|
Sign up to set email alerts
|

An aromatase‐associated cytoplasmic inclusion, the “stigmoid body”, in the rat brain: I. Distribution in the forebrain

Abstract: An aromatase-containing neural system was examined in the rat forebrain, using a polyclonal antibody against aromatase-associated human placental antigen X-P2 (hPAX-P2). Numerous dot-like structures, which we have called stigmoid bodies, were immunostained in the preoptico-hypothalamic region, the bed nucleus of the stria terminalis, the medial amygdala, the arcuate nucleus, the subfornical organ, and the area extending from the hypothalamic area to the central gray through the medial forebrain bundle and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 69 publications
(54 citation statements)
references
References 94 publications
4
49
1
Order By: Relevance
“…The highest P/S ratio of Hap1 was seen in the hypothalamus (Fig. 1B), in agreement with the finding that SBs are more abundant in the hypothalamus than in other tissues (5,10,14). Thus, these results showed that the use of a detergent-based strategy to enrich SBs in mouse brain was feasible.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The highest P/S ratio of Hap1 was seen in the hypothalamus (Fig. 1B), in agreement with the finding that SBs are more abundant in the hypothalamus than in other tissues (5,10,14). Thus, these results showed that the use of a detergent-based strategy to enrich SBs in mouse brain was feasible.…”
Section: Resultssupporting
confidence: 89%
“…For example, Hap1 is abundantly expressed in the hypothalamus, and its expression in the hypothalamus influences the central control of feeding (9); as a direct result, mice lacking Hap1 are malnourished and die in the early postnatal period (5, 10, 11). The function of Hap1 is also age dependent and appears to be important for postnatal neurogenesis in the paraventricular nuclei, the lateral hypothalamus (5, 11), and the dentate gyrus of the hippocampus (7).The specific function of Hap1 in the hypothalamus may be associated with unique cytoplasmic structures called "stigmoid bodies" (SBs), which are formed by Hap1 in the hypothalamus (12, 13) and appear to be non-membrane-bound, ovoid to circular in shape, and 0.5-3 μm in diameter (14,15). Widely regarded as a determinant marker for SBs, Hap1 is capable of sequestering several important disease-related proteins into SB-like inclusions in cell cultures, including Abelson helper integration site 1 (Ahi1), androgen receptor, TBP, and ataxin-3 (6, 16-18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…25 forebrain regions of the rat. 98 Although the subcellular functions of SBs have not yet been understood, it is important to know that SBs contain HAP1. 11,15 SBs containing HAP1 also are found to contain the unknown human placental antigen complex X-P2 (hPAX-P2) and apolipoprotein E receptor, SorLA/LR11 and sortilin (two members of the vacuolar protein sorting 10 (VPS10) domaincontaining family).…”
Section: Hap1 Regulates Recycling Of Membrane Receptors and Is Involvmentioning
confidence: 99%
“…One is the "necklace olfactory system" immunohistochemically discovered by the PAX antibody [121], and the other is an intriguing neuronal inclusion, the "stigmoid body" , which was also marked by PAX antibody and found specifically in rat preopticohypothalamus and limbic regions involved in reproductive functions [237]. The former is the only distinct unit morphologically identified in the rat primary olfactory system and it has been considered to be involved in "pheromone-induced" olfactory function associated with rat suckling behavior.…”
Section: Other Associated Structures: the Stigmoid Bodymentioning
confidence: 99%